Organic Acids, Antioxidants, and Dietary Fiber of Mexican Blackberry (Rubus fruticosus) Residues cv. Tupy. (1st April 2018) - Zafra-Rojas, Quinatzin; Cruz-Cansino, Nelly; Delgadillo-Ramírez, Alma; Alanís-García, Ernesto; Añorve-Morga, Javier; Quintero-Lira, Aurora; Castañeda-Ovando, Araceli; Ramírez-Moreno, Esther
Abstract : Blackberry fruit processing generates residues comprised of peel, seeds, and pulp that are abundant in flavonoids, colorants, and organic acids. The objective of this study was to determine the organic acids, antioxidants, and dietary fiber content of blackberry residues and compare antioxidants and dietary fiber content of a prune-based commercial product. The ABTS, DPPH, and FRAP methodologies were used for antioxidant capacity. The blackberry residues exhibited a high amount of malic acid (5706.37 mg/100 g db), phenols (4016.43 mg GAE/100 g db), and anthocyanins content (364.53 mg/100 g db) compared with the commercial product. These compounds contributed to the antioxidant capacity (by ABTS) of both products but were 20 times higher in blackberry residues. The fruit residues were able to reduce iron (by FRAP) 4.4 times compared to the prune-based product. Total dietary fiber (44.26%) and functional properties as water retention capacity (2.94 g/g), swelling capacity (5.00 mL/g), and fat absorption capacity (1.98 mL/g) of blackberry residues were significantly higher than those of the commercial sample. The results demonstrated that, due to its antioxidant compounds and functional properties, the blackberry residue can be considered a source of components with potential benefit to human health.